Building 21st century skills of multiethnic students: Studying genetic diversity in research-based exploration and the local potential of the north Maluku islands - Haerullah, Ade; Suparman, Suparman; Roini, Chumidach; Pagala, Jassia; Ariyani, Linda Fauziyah (International Journal of Innovative Research and Scientific Studies, 2025)
Biology learning in schools should be related to the environment in which students live and learn based on real or contextual problems in everyday life. Learning like this has the potential to provide meaningful experiences to students. The local potential of the region needs to be explored so that it can be utilized as teaching materials and media and learning resources. This study aims to test teaching materials for genetic diversity based on research exploring the local potential of the North Maluku archipelago region for XII grade students of MAN 1 Ternate city. The research was conducted in two stages, namely the survey stage, namely conducting local potential exploration research in the form of Drosophila melanogaster as a need assessment and the learning trial stage based on local potential exploration research. The results of data analysis show that; 1) local potential in the form of morphological characters of Drosophila melanogaster in Ternate and Tidore islands varies from the shape of the eyes, abdomen shape, abdomen color and wing shape. 2) the morphological character of Drosophila melanogaster has a small similarity coefficient index value, 3) research-based learning exploration of the local potential of the North Maluku islands can improve the 21st century skills of grade XII MAN 1 students.